Pathological markers of Piezo1 at distal anastomosed ureter in predicting pyeloplasty outcomes in children - Zhou, Jincai; Lu, Xun; Huang, Liqu; Guo, Yunfei (Frontiers in Pediatrics, 2025)
ObjectiveTo evaluate the prognostic value of Piezo1 expression in the distal anastomosed ureter for predicting pyeloplasty outcomes.MethodsDistal anastomosed ureter specimens from 28 patients diagnosed with primary ureteropelvic junction obstruction (UPJO) undergoing laparoscopic pyeloplasty were analyzed. Immunohistochemistry assessed Piezo1 expression, and Masson's trichrome staining determined the collagen-to-muscle ratio (CM ratio). Postoperative outcomes at 12 months were categorized as excellent improvement, good improvement, mild improvement, no improvement, or deterioration based on hydronephrosis severity scores (HSS). Associations between pathological markers (Piezo1 and CM ratio) and surgical outcomes were examined.ResultsThe cohort included 28 patients (22 male, 6 female), with a median age of 64.3 months (IQR: 15.4–102.6). Compared to the unsatisfactory outcome group (no improvement/deterioration), the satisfactory group (excellent/good/mild improvement) exhibited significantly lower Piezo1 expression and CM ratio in the distal anastomosed ureter. Piezo1 expression strongly correlated with CM ratio (r = 0.687, p < 0.0001). Piezo1 expression level threshold of <2.765% predicted satisfactory outcomes.ConclusionDistal anastomosed ureter Piezo1 expression is a promising prognostic biomarker for pyeloplasty outcomes.